PERUBAHAN DENYUT NADI PADA REMAJA SETELAH JOGGING DENGAN JARAK 2 KM DI TAMAN CADIKA MEDAN JOHOR - Handi Efendi (Jurnal Penelitian Kesmasy, 2019)
During the jogging activity we do, there will be a change in the pulse rate in response to transporting oxygen to the muscles that are having an activity. Jogging is the same as an exercise that can increase the pulse rate and burn calories and prevent poor lifestyle changes that are less active. This study aims to determine how much the change in pulse in adolescents after jogging with a distance of 2 KM in Cadika Park Medan Johor. The method used in this study is a survey of analytic methods with a cross-sectional design. The sampling technique is Quota (ration) of 28 respondents, the study was examined based on inclusion criteria, namely the age of 19-21 years and physically and mentally healthy. Data obtained from direct measurement of the pulse, the data is processed using computer software. After analyzing the data using the Wilcoxon test, the results were obtained which stated that there was a change in pulse rate after jogging with a distance of 2 KM in Cadika Park Medan Johor.